Empowerment of Community with the Application of Compost on the Cultivation and Post-Harvest of Onion - Warnita Warnita; Nalwida Rozen; Novizar Nazir (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Kenagarian (West Sumatra traditional village) Andaleh is located at the base of Mount Marapi in Batipuh Tanah Datar District, West Sumatra. The main livelihoods of the population are farming by planting rice, vegetable crops, ornamental plants, and cinnamon. In general, farmers in this location increase the yield of vegetables (onion) using artificial fertilizers. Sometimes it requires limited chemical fertilizer, difficult to obtain and expensive. Of course, this will burden farmers in the production of onion is a daily necessity of the community. At this location, there are many titonia plants and agricultural waste. The solution given is agricultural waste and plant processing into compost. Compost can increase growth and yield of onion bulbs. The objectives to be achieved in Community Service and Empowerment Program (KKN-PPM) activities are 1) Making compost using straw and agricultural waste and its application as organic fertilizer when mapping the red plotters, 2) Applying agricultural waste compost in the cultivation of onion 3) Processing the onion bulbs into the fried onion. The methods applied were debriefing students, counseling, training and demonstration plots with farmers. Activities that have been carried out are counseling about good onion cultivation, counseling about the benefits of organic fertilizer (compost) to 1) improve soil improvement and sources of nutrients for plants. 2) training to make compost from straw and agricultural waste using Effective Microorganism EM-4, 3) supporting compost application in onion cultivation in farmers' fields and 4) processing of fried onion.